Talent Management Transformation in the Industry 4.0 Era: A Study on Manufacturing Companies in Semarang Regency - Maharani Hulu; Dyah Palupiningtyas (International Journal of Economics and Management Research, 2024)
This research aims to explore talent management transformation in the Industry 4.0 era at manufacturing companies in Semarang Regency. Using a qualitative approach with a multiple case study design, the research involved five manufacturing companies with diverse characteristics. The results show a paradigm shift in talent conceptualization, from focusing on specific technical skills to a combination of technical, digital, and adaptive skills. Five key capability clusters (digital, adaptive, collaborative, analytical, and innovative) were identified as the focus of talent development. Adaptation strategies implemented include process digitalization, adaptive learning programs, agile performance management, strengthening employee value proposition, and developing collaborative learning ecosystems. The research also identified five main challenges: digital capability gaps, resistance to change, infrastructure and resource limitations, challenges in contextualizing global practices, and generational gaps in digital adoption. Critical success factors include leadership commitment, clear vision and strategy, holistic approach, focus on people, flexibility, data-driven decision making, and continuous learning culture. This research contributes to the talent management literature by developing a contextual capability framework for the Industry 4.0 era in the Indonesian manufacturing context, as well as providing practical guidance for organizations in navigating talent management transformation by considering both technical and socio-cultural aspects.